Inclusive Education does not Include Literacy ='s Reading + Writing - Mindy R. Carter (Canadian Society for Studies in Education, 2010)
The purpose of this paper is to consider: 1) How North American definitions and myths related to literacy have been constructed; 2) How these definitions and myths might be deconstructed; and 3) How a culturally specific and sensitive "brand" of literacy might lead to a more inclusive education for students.